Visible-light-induced controlled oxidation of N-substituted 1,2,3,4-tetrahydroisoquinolines for the synthesis of 3,4-dihydroisoquinolin-1(2h)-ones and isoquinolin-1(2H)-ones - Bansode, Ajay H.; Suryavanshi, Gurunath (Advanced Synthesis & Catalysis, 2021)
A visible light-rose bengal-TBHP mediated, controlled oxidation of N-substituted 1,2,3,4-tetrahydroisoquinolines is developed for the synthesis of 3,4-dihydroisoquinolin-1(2H)-ones and isoquinolin-1(2H)-ones. The present method feature's a broad substrate scope, good functional group tolerances, and the products were prepared in good to excellent yields. The developed methodology further demonstrated in the synthesis of isoindolo[2,1-b] isoquinolin-5(7H)-one (topoisomerase-I inhibitor).
Keywords: 2; 3; 4-Dihydroisoquinolin-1(2H)-one; 4-tetrahydroisoquinolines; Isoquinolin-1(2H)-one; N-substituted 1; Oxidation; Photocatalysis